1999
DOI: 10.1557/jmr.1999.0021
|View full text |Cite
|
Sign up to set email alerts
|

Determination of domain structure and abundance of epitaxial Pb(Zr, Ti)O3 thin films grown on MgO(001) by rf magnetron sputtering

Abstract: Epitaxial Pb(Zr x Ti 12x )O 3 (x 0.0-0.32) ferroelectric thin films of 500 nm thickness were grown on MgO(001) single crystal substrates by in situ rf magnetron sputtering, and evolution of their domain structures is characterized by employing various x-ray diffraction techniques. X-ray u-2u scan showed the films were grown highly c-axis oriented with a tetragonal perovskite structure. 90 ± domain configuration was investigated using the x-ray rocking curve analysis for PZT 100 peaks in two different f angles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…There are only a few experimental determinations of the evolution of the misfit-strain with temperature [75,[97][98][99] whereas several evolutions of the complete set of lattice parameters evolution with temperature have been reported on Pb(Zr 1-x ,Ti x )O 3 thin films (e.g., see [100,101] for monodomain films and [79,82,83,102] for polydomain ones).…”
Section: Isotropic Biaxial Stress Fieldmentioning
confidence: 99%
“…There are only a few experimental determinations of the evolution of the misfit-strain with temperature [75,[97][98][99] whereas several evolutions of the complete set of lattice parameters evolution with temperature have been reported on Pb(Zr 1-x ,Ti x )O 3 thin films (e.g., see [100,101] for monodomain films and [79,82,83,102] for polydomain ones).…”
Section: Isotropic Biaxial Stress Fieldmentioning
confidence: 99%
“…As a matter of comparison, the FWHM of our epitaxial PZT films is also much lower than previous reported values for PZT films on GaN and PZT on a YSZ buffered Si wafer . Further improvement of the crystalline quality of the PZT is limited by the lattice mismatch between MgO and PZT . This emphasizes the pivotal role of the MgO buffer layer in epitaxial growth of PZT films.…”
mentioning
confidence: 46%
“…13͒ and the domain structure was found to be 100% c domains. A polydomain structure has been reported by Lee et al, 14 with a decrease of the volume fraction of c domains ͑␣ c ͒ with increasing Ti concentration from 90% for PZT 32/ 68 down to 75% for pure PbTiO 3 . PbTiO 3 , the end member of PZT, has been studied as a thin film deposited on MgO by many authors.…”
Section: Erling Ringgaardmentioning
confidence: 57%
“…Kim et al 23 reported T C film to be 10 K higher ͑40 K lower͒ than the bulk when heating ͑cooling͒. Temperature evolution of Pb͑Zr 1−x Ti x ͒O 3 ͑x = 1 , 0.92, 0.84, 0.76, 0.68͒ thin films deposited on MgO was reported by Lee et al 14 The out-of-plane lattice parameters as well as T C film were equal to the corresponding bulk values, i.e., the films considered were strain-free.…”
Section: Erling Ringgaardmentioning
confidence: 85%